Does Living Arrangement Affect Work Status, Morbidity, and Treatment Seeking of the Elderly Population? A Study of South Indian States - Arpita Paul and Raj Kumar Verma (SAGE Open July-September, 2012)
The well-being of the elderly population in India is of prime importance in the context of a weak social security system, breakdown of family structure, and increasing noncommunicable diseases. In this context, this study aims to understand the linkages of the living arrangements of the elderly with their work status, morbidity, and treatment-seeking behavior in four states in South India. This study was based on cross-sectional secondary data from the 60th round of National Sample Survey (NSS) on “Morbidity, Health Care and the Condition of the Aged” conducted in India in 2004. A subsample of 7,853 elderly from four demographically advanced states in South India formed the study population. Results showed that most of the elderly were working as unpaid workers in their later ages. A significant number of the elderly with primary or more education and living with their children without spouse or with other relatives worked as unpaid workers. Multivariate analyses suggest that those elderly living with their children were less likely to suffer from any morbidity and more likely to seek treatment. Economic well-being and usual activity status are significant predictors of morbidity and treatment-seeking behavior. Those elderly who lived alone were more vulnerable to poor health and more likely to work for their livelihood. Irrespective of the living arrangement, treatment seeking among the elderly was relatively higher in Kerala compared with the rest of the states. Thus, the family plays a significant role in elderly care, and living arrangement affects the work status and morbidity condition of the elderly population in the states of South India.